Kreasiki Gymnastics in Reducing the Stress Level of Diabetes Mellitus Patients - Dhina Widayati; Nian Afrian Nuari (JURNAL INFO KESEHATAN, 2020)
Diabetes mellitus is a chronic disease characterized by an increase in blood glucose levels due to a disruption of the pancreas in the production of the hormone insulin. One problem for people with diabetes is unstable glucose levels, which can trigger stress. One of the diseases' management can be done with exercise that can be packaged in the form of gymnastics by combining exercise and relaxation movements. This study's objective is to determine the effect of Kreasiki gymnastics (a combination of deep breathing relaxation and dhikr or pray) on stress levels in patients with type 2 diabetes mellitus. This study used a Pre-Experiment design with a one-group method of Pre-Post Test Design. The sample size in this study amounted to 27 respondents obtained by purposive sampling. Measurement of stress levels used the modified Depression Anxiety Stress Scale (DASS-42) questionnaire. The results of the analysis with the Wilcoxon Sign Rank Test showed a p-value of 0.008, which means that the Kreasiki gymnastics affected reducing the stress level of people with diabetes mellitus. Before the intervention, most respondents had moderate stress levels, and after the response, it showed all respondents with mild stress levels. Kreasiki gymnastics can reduce stress levels in patients with type 2 diabetes mellitus. It occurs through a mechanism with two pathways, which are psychologically and physically. Psychologically, stimulation of endorphin hormone secretion will result in a relaxed condition to activate insulin. Physically, the effect of contractile muscles will absorb glucose because the insulin works more actively so that it can reduce sugar levels.